A note on migratory destinations of humpback whales from the eastern Caribbean - Stevick, Peter; Carlson, Carole; C. BALCOMB, KENNETH (J. Cetacean Res. Manage., 1999)
Identification photographs of humpback whales taken in the eastern Caribbean were compared with photographs from the North Atlantic to identify re-sightings. Nine individuals were identified in the eastern Caribbean region, seven of these in the Grenadine Islands. There were three re-sightings. Two individuals were re-sighted in northern feeding grounds: one between Newfoundland and Saba Bank; the other between Greenland and Grenada. This demonstrates movement between this breeding and calving area and two of the primary humpback whale feeding grounds in the North Atlantic. The re-sighting rate (0.222) is comparable to the rate of re-sightings between feeding grounds and other breeding areas in the North Atlantic. Another individual was re-sighted in Puerto Rico and Dominica, demonstrating an exchange between the eastern Caribbean and another breeding and calving area in the West Indies.